Dioctatin Activates ClpP to Degrade Mitochondrial Components and Inhibits Aflatoxin Production. Issue 11 (19th November 2020) - Furukawa, Tomohiro; Katayama, Hidekazu; Oikawa, Akira; Negishi, Lumi; Ichikawa, Takuma; Suzuki, Michio; Murase, Kohji; Takayama, Seiji; Sakuda, Shohei
Summary: Aflatoxin contamination of crops is a serious problem worldwide. Utilization of aflatoxin production inhibitors is attractive, as the elucidation of their modes of action contributes to clarifying the mechanism of aflatoxin production. Here, we identified mitochondrial protease ClpP as the target of dioctatin, an inhibitor of aflatoxin production of Aspergillus flavus . Dioctatin conferred uncontrolled caseinolytic capacity on ClpP of A. flavus and Escherichia coli . Dioctatin-bound ClpP selectively degraded mitochondrial energy-related proteins in vitro, including a subunit of respiratory chain complex V, which was also reduced by dioctatin in a ClpP-dependent manner in vivo . Dioctatin enhanced glycolysis and alcohol fermentation while reducing tricarboxylic acid cycle metabolites. These disturbances were accompanied by reduced histone acetylation and reduced expression of aflatoxin biosynthetic genes. Our results suggest that dioctatin inhibits aflatoxin production by inducing ClpP-mediated degradation of mitochondrial energy-related components, and that mitochondrial energy metabolism functions as a key determinant of aflatoxin production. Graphical Abstract: Highlights: Dioctatin binds to and activates ClpP Dioctatin-bound ClpP selectively degrades mitochondrial energy-related proteins Dioctatin reduces TCA cycle metabolites and raises glycolysis and ethanol production Dioctatin reduces acetylated histone and expression of aflatoxin biosynthetic genes Abstract : Furukawa et al. identified mitochondrial ClpP as the target molecule of dioctatin, an inhibitor of aflatoxin production of fungi. They revealed that dioctatin activates ClpP to degrade mitochondrial energy-related proteins, such as a component of respiratory chain complexes, which causes metabolic disturbances and reduction of aflatoxin production.